2018
DOI: 10.1152/ajprenal.00648.2017
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline attenuates cisplatin-induced acute kidney injury through pleiotropic effects

Abstract: Cisplatin (CDDP) is a widely-used chemotherapeutic drug for solid tumors, but its nephrotoxicity is a major dose-limiting factor. Doxycycline (Dox) is a tetracycline antibiotic that has been commonly used in a variety of infections. Dox has been shown to possess several other properties, including anti-tumor, anti-inflammatory, anti-oxidative, and matrix metalloproteinase (MMP)-inhibiting actions. We therefore investigated whether Dox exerts renoprotective effects in CDDP-induced acute kidney injury (AKI). Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…The latter are vital for both membrane structure maintenance and overall mitochondrial activity. As cisplatin levels increase, Bcl-2 is downregulated in response to p53 activation [87,88,89,90].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…The latter are vital for both membrane structure maintenance and overall mitochondrial activity. As cisplatin levels increase, Bcl-2 is downregulated in response to p53 activation [87,88,89,90].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…Bcl family proteins are essential for maintenance of mitochondrial function and membrane integrity. There is a strong consensus that the anti-apoptotic mitochondrial protein, Bcl-2, is downregulated in response to cisplatin [40,44,70,75,76,78,79,83,84,88,89,104,105,106,107,108,109,110,111,112,113,114,115,116,117] through p53 activation [111,113,118]. One study, however, showed that Bcl-2 mRNA is increased after administration of cisplatin [119].…”
Section: Introductionmentioning
confidence: 99%
“…Blocking of glycans with doxycycline, a broad-spectrum matrix metalloprotease inhibitor, was shown to restrict the secretion of pro-inflammatory cytokines in cisplatin and IRI-induced AKI ( 161 , 162 ). Heparanase inhibitors such as PG545 was found protective in experimental ischemic IRI ( 63 ) and is currently in clinical testing.…”
Section: Potential Therapeutic Application Of Targeting Alarmin Signamentioning
confidence: 99%